Difference in Using Protrusion Face Mask before or after Rapid Palatal Expansion in Skeletal Class III Children: A Preliminary Study - Patrizia Lucchi; Marco Rosa; Giovanni Bruno; Alberto De Stefani; Francesca Zalunardo; Antonio Gracco (MDPI AG, 2022)
Treatment of third-class malocclusions often presents a challenge for orthodontists. Skeletal disharmony is often associated with dental malposition. There are several therapeutic choices, including the use in combination of transverse expansion of the maxilla with rapid palatal expander (RPE) and posterior-anterior traction with a Delaire face mask (FM). The purpose of the study is to verify whether there are significant differences in the treatment outcome in the case of use of a face mask followed by a palatal expander or with the sequence of these auxiliaries reversed. Subject and Methods: The two groups were both made up of 13 patients, subdivided into group A, i.e., those whose sequence involved the use of extraoral traction first and then the disjunctor, and those with an inverted sequence in group B. Some cephalometric parameters and dento-skeletal characteristics were evaluated pre-treatment (t0) and at the end of therapy (t1). Results: Considering the T1-T0 of group A (Delaire + rapid palatal expander), the evaluation of the results obtained in this work allows us to observe how within group A there is a significant improvement in the Witts and Nanda indices and facial convexity. Group B (treated with the palate disjunctor sequence followed by traction with Delaire's mask) showed a significant improvement in ANB, in AoBo, and AppBpp values and in convexity. The two groups were comparable, and no statistically significant difference was highlighted. Discussion: The early therapy of the third skeletal classes by means of a rapid palate expander and face mask is effective. There is no statistically significant difference in the two groups who performed the therapy in reverse mode. This suggests that the clinician should choose the treatment sequence based on the skeletal and occlusal conditions of their patients at the start of treatment. Conclusion: Early therapy of third skeletal classes with sagittal expansion using a rapid palate expander can be performed earlier or later than posterior-anterior traction with a Delaire mask.